(untitled) (Journal of Parents and Teachers, 2024)
The article tells a story based on real events, where a family decides to set up the Nativity scene at home and keep it throughout the year, as every day the sun rises and a new day is born, just as it happened to Jesus. They also describe certain situations that resemble real life and activities that can be carried out.